2019
DOI: 10.1002/hbm.24504
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic functional network connectivity in Huntington's disease and its associations with motor and cognitive measures

Abstract: Dynamic functional network connectivity (dFNC) is an expansion of traditional, static FNC that measures connectivity variation among brain networks throughout scan duration. We used a large resting‐state fMRI (rs‐fMRI) sample from the PREDICT‐HD study (N = 183 Huntington disease gene mutation carriers [HDgmc] and N = 78 healthy control [HC] participants) to examine whole‐brain dFNC and its associations with CAG repeat length as well as the product of scaled CAG length and age, a variable representing disease b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 74 publications
(92 reference statements)
5
42
0
Order By: Relevance
“…Recent studies applying the dynamic FNC method (dFNC) have demonstrated that temporal functional network connectivity (FNC) analysis (i.e., co-activation between covarying networks estimated via independent component analysis) can uncover reoccurring connectivity patterns at resting state or during task performances. Their results also indicate that brain connectivity patterns iterate through time and show smooth variations of connectivity (Allen et al, 2014; Calhoun et al, 2014; Damaraju et al, 2014; Rashid et al, 2014; Espinoza et al, 2019). The dFNC method provides a way to explore temporally transient changes in the functional connectivity among brain networks using sliding windows to compute FNC across time (Sakoğlu et al, 2010; Allen et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies applying the dynamic FNC method (dFNC) have demonstrated that temporal functional network connectivity (FNC) analysis (i.e., co-activation between covarying networks estimated via independent component analysis) can uncover reoccurring connectivity patterns at resting state or during task performances. Their results also indicate that brain connectivity patterns iterate through time and show smooth variations of connectivity (Allen et al, 2014; Calhoun et al, 2014; Damaraju et al, 2014; Rashid et al, 2014; Espinoza et al, 2019). The dFNC method provides a way to explore temporally transient changes in the functional connectivity among brain networks using sliding windows to compute FNC across time (Sakoğlu et al, 2010; Allen et al, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Then, in each time-windowed domain a FNC vector is calculated. This procedure generates a discrete sequence of windowed FNC (wFNC) vectors that are then represented by wFNC matrices (Figure 1B) describing connectivity behavior across time (Sakoğlu et al, 2010; Allen et al, 2014; Damaraju et al, 2014; Rashid et al, 2014; Espinoza et al, 2019). Subjects’ dFNC data is formed by all wFNC vectors, and is referred to as the zero order derivatives of the sliding window correlations.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, we also assessed whether intelligence can be predicted from regional gray matter volumes when not correcting for total brain size (i.e., from absolute gray matter volumes), to test the influence of total brain size on the prediction of intelligence from regional gray matter differences. As there exists no general consensus on how to best construct meaningful features from the very high-dimensional voxel-wise neuroimaging data, we implemented two different approaches of feature construction and compared the respective results: We started with a well-established and purely data-driven method, i.e., principal component analyses (PCA, see e.g., Abreu et al 2019 ; Espinoza et al 2019 ; Wasmuht et al 2018 ). In addition, we implemented a more theoretically informed, domain knowledge-based approach, which combines voxel-specific gray matter values in regions of interest in accordance with a well-established functional brain atlas (Schaefer et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI (fMRI) studies have reinforced our understanding of limbic system dysfunction in HD. Reduced functional connectivity, network integrity and activity was found in the HD hippocampus, amygdala, ventral striatum, cingulate cortex and prefrontal cortex using different fMRI paradigms assessing verbal working memory, emotional processing, interference/conflict resolution and attention/alertness [89][90][91][92][93][94][95][96][97][98][99]. Such alterations in activity patterns produce multidimensional maps that to some extent reflect internal states of brain processing in response to a task.…”
Section: Other Limbic System Changes In Clinical Hdmentioning
confidence: 97%